IPTEKS ANALISIS HASIL LAPORAN KEUANGAN DAN ASET SULAWESI UTARA - Sipayung, Yosua Afryan Iriando; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2018)
Analysis of financial statements is a study that records financial statements of a company or government in a period and describes the results of performance on the company or government. Excess financial statements know information about financial conditions, financial capacity, and changes in company capital in the previous period. The low quality of financial statements can result in data inaccuracies that are in the company or government.. Financial statements are very important information in economic decision making. By analyzing financial statements, government accountants can determine the right in making a decision so that government goals can be achieved. In the implementation of decentralization and autonomy, regions are given the right to obtain financial resources, which include, in the form of certainty the availability of funding from the government in accordance with government affairs, authority to collect and use regional taxes and levies, the right to obtain proceeds from national resources being in the area and other balancing funds, the right to manage regional wealth and obtain other legitimate sources of income, as well as funding sources. The new paradigm changes in the management of State property / State assets which are marked by the issuance of Government Regulation No. 27 of 2014 which is a derivative regulation of Law No. 1 of 2004 concerning State Treasury, has given rise to new optimism in the arrangement and management of State assets that are more orderly, obligatory and transparent in the future. In the management of regional assets requires legal principles that can be a strong foundation in a regional asset management mechanism to avoid irregularities.Keywords: Financial statements, regional assets, funds, regulations, obligations